Religions Of Star Trek. - Kraemer, Ross Shepard, 1948- (Basic Books, 2009)
Is there a God? What evil lurks beyond the stars? Can science save one's soul? Profound questions like these have consumed human thought over the ages; they also inspired the original creators of the Star Trek canon of TV series and films. Religions of St.